EFISIENSI PEMAKAIAN PUPUK URIN MANUSIA PADA PERTUMBUHAN DAN HASIL PADI SAWAH - WIYONO WIYONO; EKO HARTOYO; MAHANANTO MAHANANTO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2015)
Dependence on chemical fertilizers (inorganic) are redundant in addition to causing the price of fertilizer is expensive and scarce in the market, has also resulted in the improper use of fertilizers (Appropriate fertilizer) that decrease the yield and productivity of the soil. The use of organic fertilizer has effective influence since it could increase the growth and yield, also capable of efficient use of inorganic fertilizers and improve soil fertility. The purposeof this researchistoreduce theuse of chemical fertilizersby addingorganic fertilizer(urine) in ricefields.The research methodis the single factorconsist of 3treatment, theuse of50% of Chemicals fertilizer by adding1000L/Ha Urine fertilizer, 75% Chemicals fertilizerby adding 1000L/HafertilizerUrine, andthe use of100% of Chemical fertilizer. Each treatmentwas repeatedeight times. The results showedthatuse of75% of Chemistry fertilizerswithadded1000 L/HaUrine fertilizersleave aresponse is notsignificantly different from theuse of 100% Chemical fertilizerson the growthand yieldof paddy, which isable to increasethe number ofproductive tillers, number of filled grain, andheavygraindryperplotwerenot significantly different